Temporal dynamics of walnut phyllosphere microbiota under synergistic pathogen exposure and environmental perturbation - Wang, Shiwei; Tan, Yu; Luo, Qing; Fang, Xinmei; Zhu, Hanmingyue; Li, Shuying; Zhou, Yujue; Zhu, Tianhui (Frontiers in Microbiology, 2025)
IntroductionPhyllosphere-associated microbes directly influence plant-pathogen interactions, and the external environment and the plant shape the phyllosphere microbiome.MethodsIn this study, we integrated 16S rRNA and ITS high-throughput sequencing to systematically investigate changes in the phyllosphere microbiome between symptomatic and asymptomatic walnut leaves affected by spot disease, with consideration of phenological stage progression. Additionally, we explored how abiotic (AT, DT, SCTCC & LPDD) and biotic factors (Pn & Gs) impact microbial communities.ResultsOur findings revealed significant differences in the diversity of the phyllosphere microbiome between symptomatic and asymptomatic leaves at the same phenological stage. Furthermore, the structure and function of phyllosphere-associated microbiome changed as the phenological stage progressed. Fungal taxa that related to the function Plant_Pathogen and bacterial taxa that related to the KEGG pathway functions Fatty acid biosynthesis and Biotin metabolism were increased in the symptomatic group. The keystone species driving the walnut phyllosphere microbiome was Pseudomonas spp., which substantially influenced the microbiome of symptomatic vs. asymptomatic leaves. Notably, Pseudomonas spp. interacted with Xanthomonas spp. and Pantoea spp. Correlation analysis revealed that the dew point temperature constituted the primary abiotic factor of phyllosphere bacterial community composition, whereas liquid precipitation depth dimension was identified as the dominant factor shaping fungal taxa. Additionally, leaf net photosynthetic rate and stomatal conductance were closely linked to the phyllosphere microbiome.DiscussionThese results advance our understanding of community-level microbial responses to pathogen invasion and highlight the multifactorial drivers of phyllosphere microbiome assembly. Ultimately, they contribute to predicting and managing walnut leaf-related diseases.